Microglial/Macrophage polarization and function in brain injury and repair after stroke - Lyu, Junxuan (CNS Neurosci Ther, 2021)
Stroke is a leading cause of disability and mortality, with limited treatment options. After stroke injury, microglia and CNS‐resident macrophages are rapidly activated and regulate neuropathological processes to steer the course of functional recovery. To accelerate this recovery, microglia can engulf dying cells and clear irreparably‐damaged tissues, thereby creating a microenvironment that is more suitable for the formation of new neural circuitry. In addition, monocyte‐derived macrophages cross the compromised blood‐brain barrier to infiltrate the injured brain. The specific functions of myeloid lineage cells in brain injury and repair are diverse and dependent on phenotypic polarization statuses. However, it remains to be determined to what degree the CNS‐invading macrophages occupy different functional niches from CNS‐resident microglia. In this review, we describe the physiological characteristics and functions of microglia in the developing and adult brain. We also review (a) the activation and phenotypic polarization of microglia and macrophages after stroke, (b) molecular mechanisms that control polarization status, and (c) the contribution of microglia to brain pathology versus repair. Finally, we summarize current breakthroughs in therapeutic strategies that calibrate microglia/macrophage responses after stroke.